2019
DOI: 10.1002/batt.201900022
|View full text |Cite
|
Sign up to set email alerts
|

Reviving Aged Lithium‐Ion Batteries and Prolonging their Cycle Life by Sinusoidal Waveform Charging Strategy

Abstract: Traditional high power constant current-constant voltage (CCÀCV) charging leads to the degradation of Li-ion batteries. Thus, aging due to charging is a primary issue to be overcome in application technology. This study proposes the impacts of a sinusoidal waveform charging strategy for charging Li-ion batteries. Specifically, a negative voltage is introduced in the charging process to reverse passivation layer formation. After few cycles of sinusoidal waveform charging, aged cells can be revived. Tests reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…The maximum of recovery capacity is about 8%. The result is consistent with that of charge-discharge machine which we have done via commercial charging instrument [12].…”
Section: Verification Of the Charging Circuitsupporting
confidence: 90%
See 2 more Smart Citations
“…The maximum of recovery capacity is about 8%. The result is consistent with that of charge-discharge machine which we have done via commercial charging instrument [12].…”
Section: Verification Of the Charging Circuitsupporting
confidence: 90%
“…The waveform is shown in Figure 1a. We have already verified and demonstrated that this composite sinusoidal waveform is effective in prolonging the 18650 lithium-ion battery life [12]. The waveform has voltage level of 3.6 V. The upper cycle and lower cycle are 0.7 V and 0.2 V, respectively.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…The performance was then evaluated by two tests: the worldwide motorcycle test cycle and new European driving cycle. The fuel reduction and kinetic efficiency enhancement can be achieved by the electrification of motorcycles; especially, the state-of-the-art charging strategy has overcome the battery aging problems [19,20]. In this study, a hybrid electric motorcycle (HEM) was developed based on a novel parallel power system architecture.…”
Section: Appl Sci 2019 9 X 3 Of 16mentioning
confidence: 99%
“…Theoretical models of passenger thermal comfort have been studied [15][16][17][18], as well as factor evaluation [19], fluidic design [20,21], simulation analysis [22][23][24], experiment [25,26], and management strategy formulation research [27]. Ever-increasing demands in low-carbon emission vehicles [28][29][30][31][32] have propelled AC development considering energy efficiency. Therefore, we introduce a novel structural design of an air outlet to approach regional AC and air exchange.…”
Section: Introductionmentioning
confidence: 99%